A review of research on education and professional development in countries with migratory potential - Francesco De Maria (Firenze University Press, 2019)
Within the framework of international strategies on issues of human development and mobility, this work is part of the scientific debate on the migration studies sector with a pedagogical perspective focusing on the migrant, on migratory aspirations, and on the educational dimension underlying the process to build a migratory project. Today, the issues of education and professional development acquire particular relevance in the sustainable management of migratory phenomena in a win-win logic that calls into question both the host countries and the countries of origin. The aim of this study is to help define effective actions that can encourage development and social and job inclusion in countries with migration potential. The paper develops the topic in question through a critical review of the literature and the research whose results are described, analysed and summarized in macro-thematic categories. We are dealing with a field that offers scientific research in the education area new topics to explore through research projects, development cooperation activities, and partnerships with those countries affected by the phenomenon of human mobility. Una sintesi di ricerca sulla formazione e lo sviluppo professionale nei paesi con potenziale migratorio Nel quadro delle strategie internazionali sui temi dello sviluppo umano e della mobilità, il presente lavoro si inserisce nel dibattito scientifico disciplinare dei migration studies con una prospettiva pedagogica che punta a dare centralità alla persona migrante, alle aspirazioni migratorie e alla dimensione formativa sottesa nel processo di costruzione del progetto migratorio. I temi della formazione e dello sviluppo professionale assumono oggi particolare rilevanza nella gestione sostenibile dei fenomeni migratori in una logica win-win che chiama in causa i paesi di accoglienza e di origine. L'obiettivo di questo studio è contribuire alla definizione di azioni efficaci e funzionali alla promozione dello sviluppo e dell'inclusione sociale e lavorativa nei paesi con potenziale migratorio. Il contributo sviluppa il tema realizzando una revisione critica della letteratura attraverso una sintesi di ricerca i cui risultati vengono descritti, analizzati e schematizzati in macro-categorie tematiche. Siamo in presenza di un campo che offre alla ricerca scientifica di area educativa nuove tematiche da esplorare attraverso progetti di ricerca, azioni di cooperazione allo sviluppo e partenariati con i paesi interessati dal fenomeno della mobilità umana